Cyperus michelianus subsp. pygmaeus (Rottb.) Asch. & Graebn: A New Record for the Flora of Nepal - Bashyal , Saroj; Pant, Deepak Raj (Journal of Plant Resources, 2024)
Sedges are among the most diverse plants and also the most difficult plants to study owing to their minute flowers arranged in complex inflorescences. It makes them vulnerable to being improperly identified or being left out during collection. The present paper aims to report a taxon of the sedges from the central lowland Cyperus michelianus subsp. pygmaeus (Rottb.) Asch. & Graebn as a new addition to the Flora of Nepal. Detailed information on this plant with description and taxonomic treatment is presented here.